Drug Utilization Profile among Outpatients with Dyspepsia at Tuan Rondahaim Regional General Hospital, Pamatang Raya, 2025 - Deviana Dorotea Pasaribu; Riana Siburian; Crismest Clara Ester Panjaitan (Jurnal EduHealth, 2026)
Changes in diet and lifestyle are one of the causes of disturbances in the digestive tract. Dyspepsia is a digestive disorder that suffers a lot and is the most common Dyspepsia can be influenced by several factors, namely increased gastric acid secretion, dietary factors, environmental factors, and psychological factors such as stress. Retrospective qualitative descriptive research with cross sectional and the sampling technique is Purposive Sampling. Samples from the study were obtained from prescription outpatient adult dyspepsia patients aged 18- 65 years at the RSUD Tuan Rondahaim Pamatang  Raya. Most sufferers of dyspepsia were female, namely 56 (56%), age range 56–65 the number of patients was 65 (65%). The drug class that is widely used is PPI with the type of drug omeprazole 20 mg in 42 patients (30%), with a frequency of 2 x 1. The most widely used dosage form wa omperazole capsule preparations, namely 42 (30%), the oral route of administration. Accompanying drugs in patients with dyspepsia, namely from the multivitamin group, namely vitamins B complex, the number of uses was 14 (22,58%) and the use of a single dyspepsia drug combination therapy is omeprazole 31 (31%), combination 2 dyspepsia drug that a lot of cytoprotective with PPI and a combination of 3 dyspepsia drug namely PPI, Cytoprotective, Prokinetic.